PEMANFAATAN EKSTRAK AKAR TUBA (DERRIS ELLIPTICA)SEBAGAI INSEKTISIDA RAMAH LINGKUNGAN UNTUKMENGENDALIKAN POPULASI ULAT BULU (LYMANTRIA BEATRIX) - dan Ardi Yuli Wardani, Eko Budiyanto, Arvana Rifki Aditya, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
This experimental research was aimed at determining the effectiveness of using tuba rootextract (Derris elliptica) on the mortality of caterpillar pests (Lymantria Beatrix) and to find out theoptimum concentration of plant‐based insecticide to reduce Lymantria Beatrix’s activity.The method used in this research included four steps, namely making of extracts, dry time test, thespray test to the leaves (to determine the damage level the leaves caused by pesticides), and testingthe larva of Lymantria Beatrix.The results of this research showed that the tuba root extract (Derris elliptica) could potentially beused as an environment friendly insecticide. Making tuba root extract using maceration process with90% ethanol solvent. Drying time test results for the standard synthetic pesticides, 100%, 75%, 50% and25% extracts, obtained results of 60 minutes, 25 minutes, 29 minutes, 40 minutes and 120 minutesrespectively. While the results of the test spray to the leaves showed that the standard syntheticpesticides causing damages to the side and the top of the leaves looked burnt and the pesticides fromTuba root extract showed the damage was only on the top of leaves that looked burnt after 6 days.Based on the results of the test to the larva of Lymantria Beatrix it could be concluded that theeffectiveness of the extract of the roots of the tuba (Derris elliptica) on the optimum mortality ofcaterpillars (Lymantria Beatrix) at a concentration of 50% with the least damage to leaves and gaveLD50 value of 69.99%.Keywords: tuba root extract, Lymantria beatrix, Botanical insecticide